Effect of the time to intervention on the outcome of thrombosed dialysis access grafts managed percutaneously - John David Prologo; Gregory Minwell; Jillian Kent; Ali Pirasteh; David Corn (Diagnostic and Interventional Radiology, 2014)

(untitled)
PURPOSEWe aimed to investigate the effect of the time interval from the clinical presentation of a thrombosed dialysis access graft to intervention on procedure success. MATERIALS AND METHODSRecords from two academic institutions for patients who underwent percutaneous thrombectomy of occluded surgical hemodialysis graft access sites in interventional radiology from 2006 to 2011 were reviewed retrospectively. The following data were recorded: gender, age, time and date of the initial request for a thrombectomy and the procedure, age of the surgical access, angiographic outcome, and clinical outcome (successful or unsuccessful postinterventional dialysis). Univariate and multivariate logistic regression were used to evaluate whether the time to intervention significantly affected the study endpoint. RESULTSIn total, 268 percutaneous thrombectomies were performed in 139 patients. Of these 224 (83.5%) were categorized as successful and 44 (16.4%) as unsuccessful. The time to intervention was 19.9±30.1 vs. 22±35 hours for successful and unsuccessful procedures, respectively. The difference between the two was not significant, and there were also no significant differences in covariate distributions between successful and unsuccessful outcomes. CONCLUSIONDuring the first 72 hours following clinical presentation of a thrombosed dialysis access graft, time to intervention may be considered independent of procedure outcome.